PROGRAMMABLE THE INTERFACE 8251A - Haryadi Haryadi; Jalinas, Skom, MM Jalinas, Skom, MM (Jurnal Sistem Komputer, 1997)
Communication is the process of sending information from one place to another, howthe delivery of information have their own modes and methods. With the computerthe way of sending information is also adjusted to the principles and workings of thecomputer.But computers can not perform data transmission without a tool that can make it ableto carry out the process of data transfer. One of these tools is the IC is an IC 8251AUSART (Universal Synchronous / Asynchronous Receiver Transmitter) is IC that isused to implement the information delivery process using serial synchronous /asynchronous.The advantage of using this chip is its ability to be programmed (programmable) inaccordance with the procedures contained in IC programming this 8251A.